Conservation and Population Status of the Lion Tailed Macaque (Macaca silenus) - A Review (Badan Pengembang Konservasi UNNES, 2022)
Lion Tailed macaque is an endangered species. They are endemic to the Western Ghats. Over the years these endangered species have been facing threats like climate change, poaching, road kills and encroachments. This unique species' survival is directly linked to ecological deterioration and destruction. An astonishing fact check revealed by IUCN states that there are about 2400-2500 Lion Tailed Macaque in the world. According to reliable sources published of late in the daily “THE HINDU” Valparai in Tamil Nadu could be the last remaining homes for the Lion Tailed macaques. Suitable conservation strategies, demographic studies and literacy campaigns on these species could help make their survival easier and smoother.